The Internalization of Religious Moderation Values on the Discipline of SMAN 13 Surabaya Students - Faradila, Hanesty; Sa’adah , Aimmatuz; Yani, Ahmad (The Future of Education Journal, 2024)
Religious education plays a strategic role in shaping students' character and personality, especially in the face of globalization and social diversity challenges. In the context of schools, the values of religious moderation become an important effort to instill tolerance and discipline in students. This study was conducted with students from SMAN 13 Surabaya as the primary respondents. The research method includes data collection techniques and direct data analysis, using structured research instruments. The results of the study and analysis significantly contribute to the formation of character, attitudes, and behaviors of students, particularly in the aspect of discipline. This study highlights the importance of the concepts of tolerance, moderation, and multiculturalism in religious education learning. Religious moderation serves as a foundation that needs to be internalized to address diversity in religion, ethnicity, language, and personal views in life. These findings emphasize that the values of religious moderation are essential to be internalized at various levels of education, from schools to universities.